Epithelial–Mesenchymal Transition (EMT) Induced by TGF-β in Hepatocellular Carcinoma Cells Reprograms Lipid Metabolism - Soukupova, Jitka; Malfettone, Andrea; Bertran, Esther; Hernández-Alvarez, María Isabel; Peñuelas-Haro, Irene; Dituri, Francesco; Giannelli, Gianluigi; Zorzano, Antonio; Fabregat, Isabel (International journal of molecular sciences, 2021)
(1) Background: The transforming growth factor (TGF)-β plays a dual role in liver carcinogenesis. At early stages, it inhibits cell growth and induces apoptosis. However, TGF-β expression is high in advanced stages of hepatocellular carcinoma (HCC) and cells become resistant to TGF-β induced suppressor effects, responding to this cytokine undergoing epithelial–mesenchymal transition (EMT), which contributes to cell migration and invasion. Metabolic reprogramming has been established as a key hallmark of cancer. However, to consider metabolism as a therapeutic target in HCC, it is necessary to obtain a better understanding of how reprogramming occurs, which are the factors that regulate it, and how to identify the situation in a patient. Accordingly, in this work we aimed to analyze whether a process of full EMT induced by TGF-β in HCC cells induces metabolic reprogramming. (2) Methods: In vitro analysis in HCC cell lines, metabolomics and transcriptomics. (3) Results: Our findings indicate a differential metabolic switch in response to TGF-β when the HCC cells undergo a full EMT, which would favor lipolysis, increased transport and utilization of free fatty acids (FFA), decreased aerobic glycolysis and an increase in mitochondrial oxidative metabolism. (4) Conclusions: EMT induced by TGF-β in HCC cells reprograms lipid metabolism to facilitate the utilization of FFA and the entry of acetyl-CoA into the TCA cycle, to sustain the elevated requirements of energy linked to this process.